Analisis Sistem Klasifikasi Keamanan dan Akses Arsip Dinamis Universitas Sebelas Maret - Khariroh, Umi (Baitul 'Ulum: Jurnal Ilmu Perpustakaan dan Informasi, 2021)
ABSTRACT Introduction. One of the four guidelines required in the dynamic archive management process is the Security Classification System and Archive Access. Its existence is needed as a guideline for managing archives in providing access services to dynamic archives. The purpose of this research is so that the public, especially the college community, can know and implement the preparation of college regulations, especially on the Classification of Security and Access to Dynamic Archives, and implement them. The Dynamic Archive Security and Access Classification System at Sebelas Maret University is regulated based on archival legislation and college archival legislation based on rector regulations. Research methods. This research uses qualitative methods with a stud library approach. Data analysis. Data is analyzed by studying books, literature, records, and various reports related to research. Results and discussion. The archiving governance of Universitas Sebelas Maret refers to government policies and regulations as well as authorized agencies such as ANRI related to archiving. The archive collection consists of textual and non-textual archives. Archives are classified into ordinary, limited, confidential and highly classified information. The classification of archives is assisted by conventional storage facilities and digital storage facilities. Conclusions and suggestions. The classification of archival access is a category of restrictions on access to archives based on the authority to use archives related to the implementation of certain tasks and functions. Archival security is a physical protection program and archival information based on its security classification. Keywords: Security System Classifications,s, Dynamic Archives.